Answer:
D.
Explanation:
Well point slope form is,
So we already have slope meaning we can plug that in for m.
And with the given point (2,-6),
we can create point slope form.
Therefore,
the answer is d. .
Hope this helps :)
D. y + 6 = -3(x - 2)
To find the equation in point-slope form, you need to use the slope and a point from that line. The slope is -3 and the point given is (2, -6).
Point-slope form is y - y₁ = m(x - x₁). Plug in the slope and point.
y - (-6) = -3(x - 2)
y + 6 = -3(x - 2)
5.7m questions
7.4m answers